Valproic Acid Enhanced Temozolomide-Induced Anticancer Activity in Human Glioma Through the p53–PUMA Apoptosis Pathway - Tsai, Hong-Chieh; Wei, Kuo-Chen; Chen, Pin-Yuan; Huang, Chiung-Yin; Chen, Ko-Ting; Lin, Ya-Jui; Cheng, Hsiao-Wei; Chen, Yi-Rou; Wang, Hsiang-Tsui (Frontiers in Oncology, 2021)
Glioblastoma (GBM), the most lethal type of brain tumor in adults, has considerable cellular heterogeneity. The standard adjuvant chemotherapeutic agent for GBM, temozolomide (TMZ), has a modest response rate due to the development of drug resistance. Multiple studies have shown that valproic acid (VPA) can enhance GBM tumor control and prolong survival when given in conjunction with TMZ. However, the beneficial effect is variable. In this study, we analyzed the impact of VPA on GBM patient survival and its possible correlation with TMZ treatment and p53 gene mutation. In addition, the molecular mechanisms of TMZ in combination with VPA were examined using both p53 wild-type and p53 mutant human GBM cell lines. Our analysis of clinical data indicates that the survival benefit of combined TMZ and VPA treatment in GBM patients is dependent on their p53 gene status. In cellular experiments, our results show that VPA enhanced the antineoplastic effect of TMZ by enhancing p53 activation and promoting the expression of its downstream proapoptotic protein PUMA. Our study indicates that GBM patients with wild-type p53 may benefit from TMZ-VPA combined treatment.